An Introduction of Genetics in Otosclerosis: A Systematic Review. (29th October 2013) - Bittermann, Arnold J. N.; Wegner, Inge; Noordman, Bo Jan; Vincent, Robert; van der Heijden, Geert J. M. G.; Grolman, Wilko
Abstract : Objective: To present an easy to read systematic review concerning the genetic etiology of otosclerosis to help health care providers in counseling otosclerosis patients more accurately. Data Sources: PubMed, Embase, CINAHL, and the Cochrane Library. Review Methods: Studies on the genetic etiology of otosclerosis were selected. Association studies and family‐based studies were included for further review. After quality assessment (risk of bias), data were extracted from the included studies. When available, odds ratios were presented. In case of corresponding genetic anomalies between the studies, it was the aim to combine results. Results: The number of available studies with low risk of bias is limited to 2 association studies and 1 family‐based study. These high‐quality studies show that otosclerosis in Japanese patients is not linked to the NOG gene and that a polymorphism in the Sp1 binding site located on the COL1A1 gene is associated with otosclerosis as well as OTSC1 . Association and family‐based studies with moderate risk of bias show a statistically significant association with the ACE gene, AGT gene, OTSC2, RELN gene, TGFB1 gene, 11q13.1, OTSC2, OTSC5, OTSC8, and OTSC10 . These results may be spurious associations due to their bias and low statistical power. Conclusion: The present systematic review shows that there is scattered evidence of limited quality and a lack of replication studies. It is not possible to point out 1 or more responsible genes, which play a key role within the genetic pathophysiologic mechanism of otosclerosis.